Determining land suitability for new primary schools in Seremban, Malaysia: an exploratory study with the GIS-MCDA approach - A Renzi, Amirul Asraf; Abdul Rasam, Abdul Rauf; Jaafar @ Ibrahim, Saiful Anuar; Echoh, Daniel Ugih (UiTM Press, 2025)
Schools serve as community cornerstones, offering education and a platform for adult learning, healthcare services, and civic engagement. Recognising this vital role, this study uses a GIS multi-criteria decision analysis (MCDA) approach to identify suitable land for a new primary school in Seremban, Negeri Sembilan. The MCDA approach assesses various critical criteria for optimal school placement, including population density, land use, school, clinic, land size, and topography or slope. The result shows that most of the land suitable for developing new schools is in the Seremban city centre due to development suitability, particularly the high population density and public facility availability. However, the study's findings also suggest that the location of the newly proposed primary schools should prioritise student accessibility and community integration in Nilai and Senawang. Ultimately, the identified land will contribute to a strong sense of community spirit and enhance the overall well-being of the area, providing valuable insights for urban planners, policymakers, and educators.